Oh My! Modula-2! / An Introduction to Programming - Cooper Doug (W.W. Norton & Company, 1990)
Preface, What are Computers, A Few Preliminaries, Changing Values, The FOR Statement, The IF Statement, The LOOP Statemet, The ARRAY Type, The RECORD Type, The Pointer Types, Files, The SET Type, Bits and Bites, Details High and Low, Index.